2015
DOI: 10.5901/mjss.2015.v6n6s6p406
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Relationship between Personal Factors and Emotional Divorce

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The factor of understanding from our study findings conforms to nurturing fondness and admiration, turning towards one another instead of away, overcoming gridlock, and creating a shared sense of meaning (Finkel, 2018;Gottman, 2015). Similar to our findings, an Iranian study's findings also points to factors like "understanding the spouse" and "understanding the spouse's situation" to be positively correlated with marital stability and satisfaction (Afrasiabi & Jafarizadeh, 2015). Looking at participants' responses, we can see that enlisted relational factors in both, good and successful marriages and reasons for divorce, fit this minding theory of love, particularly respect, reciprocity and continuity, interpersonal skills while the lack of it could be linked to the individualization factor.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The factor of understanding from our study findings conforms to nurturing fondness and admiration, turning towards one another instead of away, overcoming gridlock, and creating a shared sense of meaning (Finkel, 2018;Gottman, 2015). Similar to our findings, an Iranian study's findings also points to factors like "understanding the spouse" and "understanding the spouse's situation" to be positively correlated with marital stability and satisfaction (Afrasiabi & Jafarizadeh, 2015). Looking at participants' responses, we can see that enlisted relational factors in both, good and successful marriages and reasons for divorce, fit this minding theory of love, particularly respect, reciprocity and continuity, interpersonal skills while the lack of it could be linked to the individualization factor.…”
Section: Resultssupporting
confidence: 90%
“…Studies until now indicate different intra-personal and interpersonal or relational factors associated with marital stability and instability or divorce range personality factors (Boertien & Mortelmans, 2018;Lee & Martin, 2019) and attachment factors (Diamond, Brimhall & Elliot, 2018) to individualization (Strandell, 2018), relationship factors (Finkel, 2018;Gottman, 2015) couples' communication and interaction factors (Afrasiabi & Jafarizadeh, 2015;Mohlatlole, Sithole & Shirindi, 2018;Zaheri et al, 2016), spousal similarities in health behaviors, gene expression, immune profiles and the gut (Kiecolt-Glaser, 2018), social media, (McDaniel, Drouin & Cravens, 2017) and the minding model of love (Boniwell, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the incidence of emotional divorce may be twice that of formal divorce [37]. Although several studies have pointed to the repercussions of official divorce on mental health, both nationally and internationally [13,22], those of emotional divorce on the mental health of couples in more traditionalist societies needs further research attention.…”
Section: The Saudi Contextmentioning
confidence: 97%
“…Therefore, despite increasing acceptance and incidences of formal divorce globally (18-22%) and in Saudi Arabia (38.38% in 2020) [36], researchers opined that the incidence of emotional divorce would be higher. In fact, Afrasaibi [37] suggested that the incidence of emotional divorce could be double that of formal divorce. The present finding of 78% incidence of moderate to high levels of emotional divorce corroborates this opinion as well as findings of similar studies conducted in countries such as Iran, Jordan, and Palestine [7,27,[55][56][57] Furthermore, considering the patriarchal social structure of Saudi Arabia that affords a weaker social, economic, and legal status for women; the traditionalist religious and cultural beliefs that consider the marital relationship divine, and therefore, discourage divorce; and the social stigma associated with divorce, the high emotional divorce levels among the present sample are understandable.…”
Section: Emotional Divorcementioning
confidence: 99%